Effect of volatile compounds on the quality of miso (traditional Japanese fermented soybean paste). (March 2021) - Wang, Shuo; Liu, Xiaofang; Tamura, Takehiro; Kyouno, Nobuyuki; Zhang, Han; Chen, Jie Yu
Abstract: Optimizing the extraction of volatile compounds and establishing their effect on sensory quality are vital for understanding the quality of miso. The extraction condition were optimized using three types of sample preparation strategy (raw, solution, and supernatant), and four extraction temperatures (35, 50, 65, and 80 °C) for headspace gas chromatography–mass spectrometry (HS-GC-MS). The optimized extraction conditions used raw samples at 80 °C which reliably detected the greatest number of volatile compounds in miso. These conditions were used to identify 46 volatile compounds in the flavor profiles of miso produced from 2015 to 2018. Correlations between the detected volatile compounds and the quality rankings based on sensory evaluation showed that the intensity of most detected volatile compounds, particularly aldehydes and esters, was positively associated with miso quality. Principal component analysis on data from miso groups with different quality classifications clarified the contribution of the detected volatile compounds to miso quality. Highlights: The optimized conditions for analyzing volatiles in miso were investigated. GC-MS identified 46 volatile compounds in miso samples produced from 2015 to 2018. The impact of volatile compounds on the final quality of miso were studied. High-quality miso was considered to be associated with an intense flavor.